2020
DOI: 10.1002/jcla.23618
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin in the coronavirus disease 2019 (COVID‐19): A systematic review and meta‐analysis

Abstract: Objective The coronavirus disease 2019 (COVID‐19) has rapidly developed into a pandemic. Increased levels of ferritin due to cytokine storm and secondary hemophagocytic lymphohistiocytosis were found in severe COVID‐19 patients. Therefore, the aim of this study was to determine the role of ferritin in COVID‐19. Methods Studies investigating ferritin in COVID‐19 were collected from PubMed, EMBASE, CNKI, SinoMed, and WANFANG. A meta‐analysis was performed to compare the ferritin level between different patient g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
251
7
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(338 citation statements)
references
References 95 publications
26
251
7
17
Order By: Relevance
“…ALLY is intended to provide supplemental guidance by assessing changes in albumin and baseline lymphocyte percentage as it relates to the risk of progression to critical disease status. Other variables that were also associated with a risk for progression to critical disease status in this study and other reports included increased CRP, 17 18 ferritin, 31 neutrophil percentage, 16 17 and severe disease status on admission. 17 These variables should not be disregarded in clinical decision-making.…”
Section: Original Researchsupporting
confidence: 74%
“…ALLY is intended to provide supplemental guidance by assessing changes in albumin and baseline lymphocyte percentage as it relates to the risk of progression to critical disease status. Other variables that were also associated with a risk for progression to critical disease status in this study and other reports included increased CRP, 17 18 ferritin, 31 neutrophil percentage, 16 17 and severe disease status on admission. 17 These variables should not be disregarded in clinical decision-making.…”
Section: Original Researchsupporting
confidence: 74%
“…Ferritin is a key mediator of immune dysregulation, especially under extreme hyperferritinemia, via direct immune-suppressive and pro-inflammatory effects, contributing to the cytokine storm. Previous laboratory findings highlighted that a consistent percentage of patients with elevated serum ferritin levels faced a higher probability to experience serious complications from COVID-19 [ 30 , 31 ]. Accordingly, ferroptosis, a novel programmed cell death, has been suggested as an important cause of multiple organ involvement in COVID-19 and it might serve as a new treatment target [ 32 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequent description of raised ferritin levels and its association with a worse prognosis stand out in early reported studies of COVID-19 [ 6 ], with a reasonable parallelism with HLH (hyperferritinaemic syndrome associated with high mortality), and therefore, several studies have suggested a close relationship between severe COVID-19 and HLH [ 7 ]. In this review, we analyse the different types of hyperinflammatory syndromes associated with COVID-19, their similarities and differences with respect to HLH, and the degree of association between SARS-CoV-2 infection and HLH.…”
Section: Introductionmentioning
confidence: 99%